Suppression of tumorigenicity and metastatic potential of melanoma cells by transduction of interferon gene - Lykhova, A.A.; Kudryavets, Yu.I.; Bezdenezhnykh, N.A.; Semesiuk, N.I.; Adamenko, I.N.; Vorontsova, A.L. (Вiopolymers and Cell, 2014)
The aim of this study was to investigate an inhibitory effect of baculovirus-mediated transduction of the murine interferon-beta gene on mouse melanoma in vitro and in vivo. Methods. Studies were performed on B16 mouse melanoma (MM-4 cell line). Transduction, immunocytochemical and tumor cell biology approaches have been used in this study. Results. Transduction of MM-4 cells by the recombinant baculovirus with IFN-beta gene is accompanied by morphological changes of tumor cells, suppression of cell proliferation, significant inhibition of platting efficiency of cells and their colonies formation in semisolid agar. Moreover, transduction of melanoma MM-4 cells by the baculovirus IFN-transgene leads to inhibition of tumorigenicity and metastatic ability of the cells in vivo. The intravenous administration of recombinant baculovirus vector with IFN gene inhibits growth of metastases induced in the lungs of mice by intravenously injected tumor cells. Conclusions. Transduction of mouse melanoma cells by the recombinant baculovirus with murine IFN-beta gene inhibits their proliferative potential, tumorigenicity and metastatic activity.